Regenerative Frontiers in Craniofacial Reconstruction: Grand Challenges and Opportunities for the Mammalian Transforming Growth Factor-β Proteins - Ripamonti, Ugo; Klar, Roland M. (Frontiers in Physiology, 2010)
Science's fascination with bone and its repair processes span for thousands of years since the ancient Greek Hippocrates, the father of Medicine, made the key discovery that bone heals without scarring. Through the centuries, several lucid investigators perceived that the extracellular matrix of bone must be a reservoir of differentiating and morphogenetic factors ultimately responsible for its pronounced healing potential (reviewed in Urist, 1968, 1994; Reddi, 2000; Ripamonti et al., 2006).